The stories of English - Crystal, David (Penguin : Suffolk, 2005)
Traces the history of the English language, discussing how it envolved from a language used by only a few thousand Anglo-Saxons into one used by more than a quarter of the human race in the modern world.
Keywords: English language -- Variation; English language -- Diallects; English language -- History